(3TQM cJGH SjHhjgs - (3bGSe Hf Ydj Hf eMeO GdCfUGQj GdHWdjhSi GdUaGQs; (3SjHhjg , YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg dCf GdJCcjO EfeG WQC HYO GdJQcjH hGdGTJbGb EfeG gh bHd GdJQcjH s
(3BNQgG (B:s
(3Ccd gPG fNd ced GdSaQ GdChd ef cJGH TQM SjHhjg jJdhg Ef TGA Gddg ai Chd GdKGfi HGH EVeGA GdaYd GdeSJYed EXgGQg HYO MQa s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , JGeI s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs